La relectura positiva de la tradición poética griega en el Banquete de Platón - Soares, Lucas (PLATO JOURNAL, 2018)
The Platonic reevaluation of traditional poetry in positive terms that we read in the Phaedrus, in as much as it is conceived therein as a valuable educational resource for posterity (Phaidr. 245a1-5), does not strictly imply anything new in the Platonic corpus, but rather a systemization and complementation of a set of ideas about the origin and function of poetry that Plato had already shared in some of his early, transitional and late dialogues. From this broad set of ideas, I am interested in this study in concentrating especially on a series of passages taken from the Symposium, in order to compile two lines of analysis in this paradigmatic late dialogue which, I understand, constitute a clear precedent for the positive conception that Plato finally assumes about traditional poetry in the Phaedrus.